Dimensions of University Evaluation According to Rating Scales: Perception of Latin American Experts; [Dimensiones de la Evaluación de Universidades Según Escalas de Valoración: Percepción de Los Expertos Latinoamericanos] - Abello-Romero, J (HISIN (History of Information Systems), 2024)
Introduction: Academic indexes for evaluating universities have emerged in higher education to satisfy the demand for information and foster transparency, although they have also generated criticism. This study explores the perception of experts from Latin American universities on the dimensions used in these rankings, in order to guide future proposals. Methodology: The research is descriptive and quantitative in nature. Methodologies of thirteen rankings were analysed and a Likert scale questionnaire was applied to 712 participants from 13 Latin American countries. Results: Respondents rated the dimensions evaluated positively, although there were significant variations according to hierarchical role and country of origin. Academics prioritise research less than middle managers, and notable differences were found, especially in Argentina. Conclusions: Perceptions of the rankings vary considerably according to position and national context, suggesting the need to adapt evaluation criteria to regional realities in order to improve the relevance of these indices in Latin America. © 2024, HISIN (History of Information Systems). All rights reserved.